2017
DOI: 10.1007/s11166-017-9253-3
|View full text |Cite
|
Sign up to set email alerts
|

Improving one’s choices by putting oneself in others’ shoes – An experimental analysis

Abstract: This paper investigates how letting people predict others' choices under risk affects subsequent own choices. We find an improvement of strong rationality (risk neutrality) for losses in own choices, but no such improvement for gains. There is no improvement of weak rationality (avoiding preference reversals). Overall, risk aversion in own choices increases. Conversely, for the effects of own choices on predicting for others, the risk aversion predicted in others' choices is reduced if preceded by own choices,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…After that, the loss and mixed prospects were asked in random order. Li et al (2015) and Vieider et al (2015) also recommended to have gain questions preceding loss questions for this reason. Moreover, Etchart- Vincent and l'Haridon (2011) and Vieider et al (2015) tested for order effects between gains and losses in this regard, and found none.…”
Section: Stimulimentioning
confidence: 99%
See 1 more Smart Citation
“…After that, the loss and mixed prospects were asked in random order. Li et al (2015) and Vieider et al (2015) also recommended to have gain questions preceding loss questions for this reason. Moreover, Etchart- Vincent and l'Haridon (2011) and Vieider et al (2015) tested for order effects between gains and losses in this regard, and found none.…”
Section: Stimulimentioning
confidence: 99%
“…Applications of the QALY model often assume expected utility (EU) theory to hold. However, it is by now well-known that EU has limited descriptive validity in many domains, including in health Llewellyn- Thomas et al, 1982;Treadwell and Lenert, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Pluralistic ignorance, by contrast, is a very common misperception that occurs when a majority of people may wrongly consider that they are in the minority although their attitudes or behaviours are more representative than they presume [20,21]. Finally, false uniqueness may occur when an individual considers that his/her attitude or behaviour is more particular than others [19,22].…”
Section: The Concept Of Misperceived Social Norms Theory Applied In Tmentioning
confidence: 99%
“…Sections 4 and 5 respectively describe our main hypotheses and the experimental 1 Usually the task used to study decision making in behalf of others in a risky context is a lottery-choice with a positive expected value. A few exceptions are (Shupp & Williams, 2008;Pahlke, Strasser, & Vieider, 2015;Li, Rohde, & Wakker, 2017), who consider lotteries in different domains and for different probability levels.…”
Section: Introductionmentioning
confidence: 99%